The Use of Wordlwall in the Implementation of Teaching Modules for the Independent Curriculum to Improve Learning Outcomes of High School Class X Students - Saputri, Kaysa Syani El Safir; Oktavia, Eka Widyawati (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
This study aims to develop and implement the use of the Wordwall application as an interactive learning medium in the Kurikulum Merdeka teaching module to improve the learning outcomes of 10th- grade high school students. The research used the Research and Development (R&D) method with the ADDIE model. The findings indicate that integrating Wordwall into the learning process can enhance student engagement and learning outcomes. Therefore, Wordwall has proven to be effective in supporting Kurikulum Merdeka by creating interactive, enjoyable, and student-relevant learning experiences.